Peserta Pendidikan Profesional Guru (PPG) Matematika Dilihat dari Technological Pedagogical Content Knowledge (TPACK) - Yopi Romafilani; Nenden Wulan Lailasari; Neneng Aminah; Laelasari Laelasari (CV. AFDIFAL MAJU BERKAH, 2024)
Teachers and prospective teachers are required to carry out learning to master and continue to develop Pedagogical Content Knowledge (PCK) competencies, even now they are required to master technology and then PCK competencies are developed into Technology Pedagogical Content Knowledge (TPACK). A mathematics teacher must of course master mathematical skills because this is the main asset for teaching the material. This research aims to analyze the perceptions of in-service PPG participants regarding the professionalism of mathematics teachers based on the TPACK framework. This research is a qualitative research. The subjects of this research were 7 prospective mathematics teachers from 30 participants, where the sample was taken by sampling, namely by taking participants from vocational school teachers on the grounds that participants who taught vocational schools had challenges where the students' orientation was ready to work so they were less enthusiastic about mathematics lessons. The research data is in the form of findings from an analysis of prospective teachers' mathematical ability profiles. It is hoped that these findings can be used as a basis for further theory.